Upaya Meningkatkan Keterampilan Berbicara Dan Motivasi Belajar Peserta Didik Dengan Strategi Sosiodrama Pada Muatan Bahasa Indonesia Kelas III - Siti Rohmawati (Pedir Research Institute, 2022)
Sociodrama strategy in the form of classroom action research. The reason for choosing this strategy is with the consideration that this strategy is considered more effective and more efficient to be applied in learning speaking skills. It is said to be effective because the implementation of the sociodrama strategy will save more time, this is because students can practice speaking in groups. Meanwhile, it is said to be efficient because the learning process at MI is mostly done by playing while learning or learning while playing. The research design using a cycle includes planning, implementing actions, observing or observing the implementation of actions, and reflecting. Classroom action research consists of three cycles, each cycle consists of 1 meeting. While the data analysis using Miles and Hubarman analysis. By using sociodrama strategies on speaking skills, students are able to communicate effectively and efficiently in accordance with applicable ethics, both orally and in writing. Through the application of sociodrama strategies in Indonesian language lessons, students' speaking skills have increased. Through the implementation of sociodrama strategies in Indonesian language lessons, students' learning motivation has increased. The success of students' learning motivation has increased by reaching a percentage of 90.20% with good criteria. It means that the application of sociodrama strategy in Indonesian language lessons can increase students' learning motivation by 6.87%. The percentage in the first cycle was 77.70%, in the second cycle it reached 83.33%, while in the third cycle it reached 90.20% with good criteria.